Synthesis of hexaphenylbenzene-based template assembled synthetic proteins - Madhu, Suresh; Madica, Krishnaprasad; Gonnade, Rajesh; Sanjayan, Gangadhar J (Tetrahedron Letters, 2019)
Template-assembled synthetic proteins (TASPs) synthesized from rigid templates have attracted attention due to their interesting structural architectures and potential biomedical applications. Herein, we report the design, synthesis and characterizations of TASPs based on hexaphenylbenzene template (HPB) having twelve peptide attachable axial-arms in its structure. The peptides were attached to all the axial-arms of the template in a single step using simple solution phase peptide coupling strategy. The reaction conditions were standardized systematically using simple amines from smaller size to larger ones. (C) 2019 Elsevier Ltd. All rights reserved.